Penatalaksanaan Fisioterapi Kasus Carpal Tunnel Syndrome Pada Pekerja Kantoran - Eko Guspriadi; Catherine Hermawan Salim; Erni Selfiyan Laowo; Sehab Sodik; Jerry Maratis (LPPM Universitas Abdurrab, 2022)
ABSTRACT Objective: The focus of this case report is the management of physiotherapy in the case of carpal tunnel syndrome in office workers. Method: Pre and post test. Patient by the name of Mr. JR 34-year-old man is an office worker. On January 27, the patient came to the Esa Unggul Physiotherapy clinic complaining of pain and tingling in the wrist. Interventions given by physiotherapy include the use of orthosis, TENS modalities, US, manual therapy techniques, and exercise therapy. Results: On the VAS value of motion pain, press, and be quiet the value of each before the intervention: 7-8-3, after the intervention: 2-3-0. Radial-ulnar ROM deviation and dorsi-palmar flexion before intervention S = 600-00-500 and T = 300-00-200, after intervention S = 650-00-700 and T = 450-00-400. Muscle strength was assessed by MMT: ulnar deviation, radial deviation, palmar flexion, dorsi flexion before intervention: 4-4-3-4, after intervention: 5-5-4-5. Conclusion: Use of orthosis, TENS modality, US, manual therapy techniques, neuromobiliation, and exercise therapy are effective in reducing pain, muscle strength, increasing ROM and increasing functional activity in cases of carpal tunnel syndrome.